2017
DOI: 10.18520/cs/v113/i10/2004-2013
|View full text |Cite
|
Sign up to set email alerts
|

Can Developmental Interventions Reduce Households’ Vulnerability? Empirical Evidence from Rural India

Abstract: Vulnerability is a multidimensional concept incorporating notions of risk and poverty. While it has been established that higher incidence of poverty in developing countries exacerbates vulnerability, the role of risk requires closer inspection. Developmental interventions in these countries target poverty reduction, which in turn, could reduce vulnerability. However, a key question is whether developmental interventions reduce the vulnerability and risks faced by households. To answer this, the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Moreover, the findings of the study showed that an increase in age would increase the chances to adopt the CC adaptations. Inversely, the negative sign of the coefficient for wheat's yield specifies that with the increasing age, the capacity to work also goes down and these arguments are maintained by [51,55,68,78], conversely, outcomes of [79] opposed this. Results show that total landholding and time spent by the HHH on-farm could have a positive and significant impact on the yield of adapters, implying an increase in the values of these both parameters would increase farm productivity overtime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the findings of the study showed that an increase in age would increase the chances to adopt the CC adaptations. Inversely, the negative sign of the coefficient for wheat's yield specifies that with the increasing age, the capacity to work also goes down and these arguments are maintained by [51,55,68,78], conversely, outcomes of [79] opposed this. Results show that total landholding and time spent by the HHH on-farm could have a positive and significant impact on the yield of adapters, implying an increase in the values of these both parameters would increase farm productivity overtime.…”
Section: Discussionmentioning
confidence: 99%
“…ESR is a parametric approach, which addresses the problem of selective biased and missing unobserved characteristics, which influence the decision to adopt the adaptation to CC [66][67][68][69][70]. It follows the two-stage analysis.…”
Section: Endogenous Switching Regression (Esr)mentioning
confidence: 99%
“…There could be either positive or negative relationship for household size, and dependency ratio is the major factor for deciding the sign of the association. Several studies found a positive coefficient value, i.e., a directly proportional association between household size and impact (Bahinipati, 2016;Patnaik et al, 2016Patnaik et al, , 2017. Similar observation (positive/negative) is also anticipated for age of the HH.…”
Section: This Study Has Adopted Vulnerability As Uninsured Risk (Ver)...mentioning
confidence: 52%
“…Both idiosyncratic and covariate risks and shocks are a part and parcel of the farm households' livelihood in a developing nation like India, and these are negatively affecting their well-being, particularly those in the lower quintiles (Bahinipati, 2016;Patnaik et al, 2016Patnaik et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation